2023
DOI: 10.1371/journal.pone.0283036
|View full text |Cite
|
Sign up to set email alerts
|

Feeding practices, dietary adequacy, and dietary diversities among caregivers with under-five children: A descriptive cross-section study in Dodoma region, Tanzania

Abstract: Introduction Suboptimal feeding practices among caregivers contribute to nutritional-related health problems in children in low and middle-income countries, such as Tanzania. The continuum of the recommended feeding practices has been an utmost challenge among caregivers during the transition from health facilities to homes for improved under-five children’s health. Objective This study assessed feeding practices, dietary diversities, and dietary adequacy among caregivers with under-five children in the Dodo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…As shown in Table 1 , the study involved 312 out of 12,584 randomly sampled adults in the Dodoma region. As it has also been used by some previous studies (Millanzi, 2022 ; Millanzi et al., 2020 , 2021 ; Millanzi, Herman, & Ambrose, 2023 ; Millanzi, Herman, & Mtangi, 2023 ; Millanzi, Osaki, et al., 2023 ; Mwanja et al., 2023 ; Shitindi et al., 2023 ), a proportionate formula was adopted based on the available number and level of health facilities that were stratified into dispensaries ( n = 1: in one district) health centres ( n = 2: in three districts), district hospitals ( n = 2: in 6 districts) and referral hospital ( n = 1: in Dodoma region). A simple random sampling technique by lottery methods was used to get study participants.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…As shown in Table 1 , the study involved 312 out of 12,584 randomly sampled adults in the Dodoma region. As it has also been used by some previous studies (Millanzi, 2022 ; Millanzi et al., 2020 , 2021 ; Millanzi, Herman, & Ambrose, 2023 ; Millanzi, Herman, & Mtangi, 2023 ; Millanzi, Osaki, et al., 2023 ; Mwanja et al., 2023 ; Shitindi et al., 2023 ), a proportionate formula was adopted based on the available number and level of health facilities that were stratified into dispensaries ( n = 1: in one district) health centres ( n = 2: in three districts), district hospitals ( n = 2: in 6 districts) and referral hospital ( n = 1: in Dodoma region). A simple random sampling technique by lottery methods was used to get study participants.…”
Section: Methodsmentioning
confidence: 99%
“…The tools were confirmed to be clear and no further editing and deletion of the items were done, but it was translated into the Swahili language to blend to the literacy level of the study participants. As suggested by previous scholars (Millanzi, Herman, & Ambrose, 2023 ; Millanzi, Herman, & Mtangi, 2023 ; Mwanja et al., 2023 ; Shitindi et al., 2023 ), the data collection tool was pre‐tested among 30 adults aged 18 years and above at a different location from where the actual data collection was conducted to assure its validity and reliability. Respondents filled all items in the questionnaires entirely.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 , fifty-six respondents were not involved in the study and therefore, 324 respondents were finally analyzed. As recommended by previous scholars [ 22 , 23 ], the sample was proportionally distributed in stratum based on the selected secondary schools, classes, and year of study based on the number of students using the proportionate formula [ 24 ] .
Fig.
…”
Section: Methodsmentioning
confidence: 99%
“…Chi-square and cross-tabulation were used to determine the relationship between variables. As it has been used by previous studies [ 30 , 31 ] shown in the statistical formula number two (2), a binary and multinomial logistic regression model was performed to determine the association between the predictor variables and the outcome of interest under study at a 95% confidence interval and a 5% significance level.…”
Section: Methodsmentioning
confidence: 99%